2020
DOI: 10.21203/rs.3.rs-21150/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Rational Design of Pseudomonas putida KT2440 capable of Anaerobic Respiration

Abstract: Pseudomonas putida KT2440 is a metabolically versatile, HV1-certified, genetically accessible, and thus interesting microbial chassis for biotechnological applications. However, its obligate aerobic nature hampers production of oxygen sensitive products and drives up costs in large scale fermentation. The inability to perform anaerobic fermentation has been attributed to insufficient ATP production and an inability to produce pyrimidines under these conditions. Addressing these bottlenecks enabled growth under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Additional mutation of negative regulators, such as PtxS, which regulates 2KGA metabolism (del Castillo et al, 2008;Daddaoua et al, 2010;Udaondo et al, 2018), or Cra, might also add to the alleviation of limited intracellular carbon flux of KT2440 in the case of anoxic catabolism of glucose and fructose, respectively. Nevertheless, improving the carbon flux would only be a part of the puzzle: an in-silico approach by Kampers et al (2021) revealed that genetic and metabolic engineering to enable a facultatively anaerobic lifestyle in KT2440 was a much more elaborate process than previously thought. Thus, substitution of oxygendependent reactions to acclimate the cell to anoxic environment of the BES should also be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Additional mutation of negative regulators, such as PtxS, which regulates 2KGA metabolism (del Castillo et al, 2008;Daddaoua et al, 2010;Udaondo et al, 2018), or Cra, might also add to the alleviation of limited intracellular carbon flux of KT2440 in the case of anoxic catabolism of glucose and fructose, respectively. Nevertheless, improving the carbon flux would only be a part of the puzzle: an in-silico approach by Kampers et al (2021) revealed that genetic and metabolic engineering to enable a facultatively anaerobic lifestyle in KT2440 was a much more elaborate process than previously thought. Thus, substitution of oxygendependent reactions to acclimate the cell to anoxic environment of the BES should also be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%